Rate of reoperation after strabismus surgery - Heba Metwally (Journal of Medicine in Scientific Research, 2022)
Aims To determine and analyze the reoperation rate during the first 1–2 years following surgical correction of strabismus using the conventional suture technique. Patients and methods This retrospective cohort study included patients of all ages who underwent surgical correction of strabismus with the conventional suture technique. Electronic medical records of the patients were reviewed. The extracted data included the patients' sociodemographics, the type of strabismus, history of the first strabismus surgery, presence of sequelae, and the need for reoperation. Results This study included 337 patients who underwent surgical correction of strabismus. Thirty (8.9%) out of 337 patients required reoperation. The reoperation rate was 11/102 (10.8%) for exotropia, 9/111 (8.1%) for esotropia, and 9/112 (8%) for intermittent exotropia. The reoperation rate was 10.5% after the second operations compared with 8.6% after primary surgical corrections, with no significant difference (P = 0.637). The highest reoperation rate was in infants aged 1 year or younger (14.3%), followed by children aged 5–18 years (9.2%). The reoperation rate was 6.9% in adults who were 19–39 years old and 8.3% in the older age group (40–66 years). Conclusions The use of conventional sutures for strabismus surgery was associated with an overall reoperation rate of 8.9%. Second-time operations tended to be associated with a slightly higher rate of reoperation than the first ones. The reoperation rate was much higher in infants than in children aged 5–18 years. In adults, the reoperation rate showed a tendency to increase in older adults aged 40–66 years. The reoperation rate varies according to the type of deviation.